Kecemasan dan Kualitas Tidur Berhubungan Dengan Lama Menjalani Hemodialisa Pada Pasien Gagal Ginjal Kronik - Mevi Lilipory (MOLUCCAS HEALTH JOURNAL, 2019)
Chronic kidney disease is a progressive and irreversible decreasing in kidney function. Therapy that can be done in chronic renal disease is hemodialysis. Patients who have undergone hemodialysis for a long time experience various problems as a result of kidney disease. This study aims to determine the relationship of anxiety with the length of time undergoing hemodialysis patients with chronic kidney disease. The relationship of quality sleeping with the length of undergoing hemodialysis patients with chronic kidney disease, in RSUD dr. M. Haulussy Ambon. This study is a type of analytical research with a Cross Sectional approach. The sampling technique uses accidental sampling technique with a total sample of 43 respondents. Data analysis is performed by testing the Chi Square statistical test. The results of the anxiety variable test with the duration of undergoing hemodialysis are obtained (p = 0.002), the variable sleep quality with duration of undergoing hemodialysis is obtained (p = 0.003). Thus it can be concluded that there is a significant relationship between anxiety and sleep quality with the length of undergoing hemodialysis in RSUD dr. M. Haulussy Ambon. Suggestions for this study for nurses, can provide more motivation and attention for patients, so patients can control the anxiety and regulate patient sleep patterns, for patients are expected to increase the knowledge and motivate themselves to accept the situation so that it can minimize anxiety and perceived sleep quality. For further researchers, this research can be done further by observing other variables that related with this study.Keywords: Duration of Hemodialysis, Anxiety, Sleep Quality, Chronic Kidney Disease